Forecasting total fertility rates for urban and rural areas in Pakistan with a coherent functional modelForecasting total fertility rates for urban and rural areas in Pakistan with a coherent functional model - Waseem, Hira Fatima; Farah Yasmeen (Journal of the Pakistan Medical Association, 2023)
Objective: To project total fertility rates for urban and rural areas in Pakistan up to 2027 with 80% prediction intervals. Method: The secondary-data study was conducted from March 2020 to August 2020 at Data Bank in the Department of Statistics, University of Karachi, Pakistan, and comprised publicly available data of the Pakistan Demographic Survey from 1984 to 2007. Two statistical models, the functional time series model and the coherent functional model, were used to make the predictions about age-specific fertility rates. The forecasting performance of the models was compared through error measures. Data was analysed using R version 3.6.3. Results: The predicted total fertility rate was 1.7 (80% prediction interval: 0.4-4.4) births per woman for urban areas and 2.2 (80% prediction interval: 0.6-5.3) births per woman for rural areas in 2027 using coherent functional model. The total fertility rate predicted by the functional time series model was 2.1 (80% prediction interval: 1.6-2.6) births in urban areas and 2.7 (80% prediction interval: 1.7-4.1) births per woman in rural areas. The empirical comparison of forecast error measures obtained from the two models indicated that the coherent functional model performed better for forecasting total fertility rates for urban and rural areas in Pakistan. Conclusion: The projection of fertility rate obtained by the functional time series model and the coherent functional model described the future fertility behaviour of urban and rural populations. Key Words: Fertility, Forecast, Urban Population, Rural population, Age-specific fertility rates, Women.